E-Governance and its Role in Improving the Performance of Public Institutions Services in Libya (2002-2014) - Ambarak, Salem; Wali, Taha; Abdul Samad, Abdul Qader (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The study aims to find out the reality of the application of public electronic administration in Libya and the obstacles it faces. While the problem of the study tries to investigate the reasons for the low applications of public electronic administration in Libya, its poor performance and the lack of expansion of its uses in government institutions, as for the methodology of the study, it is descriptive and analytical and reliable in evaluating the use of technology in public administrations in Libya, and identifying the theoretical foundations of electronic management and its applications. The study concluded that the reasons for the poor level of provision of electronic services in government institutions are due to the weakness of the information and communication infrastructure, and that there is an absence in modern legislation and security policies to regulate and protect information services; In addition to the administrative and structural modernization of the various government institutions and organizations in the country to keep pace with the transformation towards electronic management.